The ecology of Anopheles mosquitoes under climate change: case studies from the effects of deforestation in East African highlands - Afrane, Yaw A.; Githeko, Andrew K.; Yan, Guiyun (Annals of the New York Academy of Sciences, 2012)
Climate change is expected to lead to latitudinal and altitudinal temperature increases. High-elevation regions such as the highlands of Africa and those that have temperate climate are most likely to be affected. The highlands of Africa generally exhibit low ambient temperatures. This restricts the distribution of Anopheles mosquitoes, the vectors of malaria, filariasis, and O'nyong'nyong fever. The development and survival of larval and adult mosquitoes are temperature dependent, as are mosquito biting frequency and pathogen development rate. Given that various Anopheles species are adapted to different climatic conditions, changes in climate could lead to changes in species composition in an area that may change the dynamics of mosquito-borne disease transmission. It is important to consider the effect of climate change on rainfall, which is critical to the formation and persistence of mosquito breeding sites. In addition, environmental changes such as deforestation could increase local temperatures in the highlands; this could enhance the vectorial capacity of the Anopheles. These experimental data will be invaluable in facilitating the understanding of the impact of climate change on Anopheles.
openalex: W1553045567 mag: 1553045567
Keywords: openalex:import

Progress towards understanding the ecology and epidemiology of malaria in the western Kenya highlands: Opportunities and challenges for control under climate change risk - Githeko, Andrew K.; Ototo, Ednah N; Yan, Guiyun (Acta Tropica, 2012)
Following severe malaria epidemics in the western Kenya highlands after the late 1980s it became imperative to undertake eco-epidemiological assessments of the disease and determine its drivers, spatial–temporal distribution and control strategies. Extensive research has indicated that the major biophysical drivers of the disease are climate change and variability, terrain, topography, hydrology and immunity. Vector distribution is focalized at valley bottoms and abundance is closely related with drainage efficiency, habitat availability, stability and productivity of the ecosystems. Early epidemic prediction models have been developed and they can be used to assess climate risks that warrant extra interventions with a lead time of 2–4 months. Targeted integrated vector management strategies can significantly reduce the cost on the indoor residual spraying by targeting the foci of transmission in transmission hotspots. Malaria control in the highlands has reduced vector population by 90%, infections by 50–90% in humans and in some cases transmission has been interrupted. Insecticide resistance is increasing and as transmission decreases so will immunity. Active surveillance will be required to monitor and contain emerging threats. More studies on eco-stratification of the disease, based on its major drivers, are required so that interventions are tailored for specific ecosystems. New and innovative control interventions such as house modification with a one-application strategy may reduce the threat from insecticide resistance and low compliance associated with the use of ITNs.
openalex: W2152725964 mag: 2152725964
Keywords: openalex:import

Malaria Transmission in the African Highlands in a Changing Climate Situation: Perspective from Kenyan Highlands - Afrane, Yaw A.; Githeko, Andrew K.; Yan, Guiyun (2011)
Vector-borne diseases are among the diseases that have been linked with climate change (IPCC. 2001). Malaria is probably the deadliest climate sensitive vector-borne disease (Githeko et al. 2000). About 90% of the 300-500 million cases of the reported malaria cases worldwide come from Africa. In the late 80s to the 90s, malaria epidemics occurred frequently in western Kenya highlands, often taking the population by surprise. The epidemics were caused by Plasmodium falciparum and transmitted by Anopheles gambiae and Anopheles funestus. Epidemics were associated with high morbidity and mortality in all age groups, with prevalence of the disease rising from about 20% to about 60%. The case mortality in functional health facilities were estimated at about 7.5% (Githeko and Ndegwa 2001). The malaria transmission system involves a complex interaction between humans, mosquitoes, the plasmodium parasite, climate and the physical environment. Warming of the climate is expected to lead to latitudinal and altitudinal temperature increase. The temporal and spatial changes in temperature, precipitation and humidity that are expected to occur under different climate change scenarios will affect the biology and ecology of vectors and intermediate hosts and consequently the risk of disease transmission. The risk increases because, although arthropods can regulate their internal temperature by changing their behaviour, they cannot do so physiologically and are thus critically dependent on climate for their survival and development (Lindsay and Birley 1996). Temperature is inversely related to altitude, thus the high-elevation areas in Africa, or highlands, generally exhibit low ambient temperature, which restricts the development of vectors and parasites. Because malaria transmission rate is temperature-dependent, any factor that alters the temperature in the highland would reduce the duration of parasite development, larval development and increase the mosquito biting rates, and subsequently increase malaria transmission in the highlands.
openalex: W1547280820 mag: 1547280820
Keywords: openalex:import

Adapting to Climate Change in Africa:Opportunities for Africa to Participate and Benefit from Investment in Adaptation for Sustainable Development. - Njenga, Cecilia; Githeko, Andrew K.; Yanda, Pius Z.; Ruppel, Oliver C.; Balgis, O.; Ojjo-Massawa, E. (2011)
openalex: W2796261915 mag: 2796261915
Keywords: openalex:import

Africa Climate Change 2007: Impacts, Adaptation and Vulnerability: Contribution of Working Group II to the Fourth Assessment Report of the Intergovernmental Panel on Climate Change - Boko, Michel; Niang, I.; Nyong, Anthony; Vogel, Andrea Isabella; Githeko, Andrew K.; Medany, M.A.; Osman-Elasha, Balgis; Tabo, Ramadjita; Yanda, Pius Z. (2018)
Climate Change 2007 – Impacts, Adaptation and Vulnerability provides the most comprehensive and up-to-date scientific assessment of the impacts of climate change, the vulnerability of natural and human environments, and the potential for response through adaptation. The report: • evaluates evidence that recent observed changes in climate have already affected a variety of physical and biological systems and concludes that these effects can be attributed to global warming; • makes a detailed assessment of the impacts of future climate change and sea-level rise on ecosystems, water resources, agriculture and food security, human health, coastal and low-lying regions and industry and settlements; • provides a complete new assessment of the impacts of climate change on major regions of the world (Africa, Asia, Australia/New Zealand, Europe, Latin America, North America, polar regions and small islands); • considers responses through adaptation; • explores the synergies and trade-offs between adaptation and mitigation; • evaluates the key vulnerabilities to climate change, and assesses aggregate damage levels and the role of multiple stresses. This latest assessment by the IPCC will form the standard scientific reference for all those concerned with the consequences of climate change, including students and researchers in ecology, biology, hydrology, environmental science, economics, social science, natural resource management, public health, food security and natural hazards, and policymakers and managers in governments, industry and other organisations responsible for resources likely to be affected by climate change
openalex: W3185851976 mag: 3185851976
Keywords: openalex:import

Adapting to Climate Change in Africa - Ruppel, Olivier; Francis, J.; Nogoye, T.; Githeko, Andrew K.; Yanda, Pius Z.; Ngana, J.; Gwary, D. M.; Zakieldeen, Sumaya; Ngana, T.; Ojjo-Massawa, E. (2011)
openalex: W2396079771 mag: 2396079771
Keywords: openalex:import